THE ADAPTATION TO A BUREAUCRATIC SYSTEM AND THE OCCURRENCE OF A NEW GENERATION IN ISAN BEFORE THE REVOLUTIONARY 1932 - Saisanguanwong, Prawit (CRMA Journal of Humanities and Social Sciences, 2020)
This article aims to study the adaptation of the traditional local power groups in Isan to a bureaucratic system before the revolutionary 1932 and how it resulted in the emergence of a new generation in Isan as well as important ideas of a new generation who was a new social power in Isan. The findings from the study indicates that under the rule of Siam’s absolute monarchy, “bureaucratic system” was the key of state mobilization. The circumstance attracted part of people in Isan to become “bureaucrats”. The traditional local power groups utilized their influences to pave the way into the administration. Most of these people were high-ranking bureaucrats in the administration. While a new generation of bureaucrats who only relied on their education to pave the way to the bureaucratic system was in medium and low positions. The new generation was concerned about the importance of education and, thus, confident in their capacity. Moreover, with civil consciousness installed by the state, they viewed themselves and people in their communities as part of the absolute monarchy state who were entitled to receive good welfare from the state. These people became a new social power who started to raise questions about circumstances of their local areas and to present problems and plans for the development of Isan to wider audience.